Networking behaviours and managers` career success in the Malaysian public service : the moderating effect of gender. - Mohd Rasdi, Roziah; Garavan, Thomas N.; Ismail, Maimunah (Emerald Group Publishing Ltd., 2013)
Purpose: This paper aims to examine the relationships between networking behaviours objective and subjective career success, and the moderating role of gender on these relationships among Malaysian public sector managers. Design/methodology/approach: The study utilised a cross-sectional design and surveyed 288 randomly selected public sector managers who were employed full-time. Findings: Increasing internal visibility was the only form of networking that related to both monthly gross incomes and subjective career success. Gender did not moderate the relationships between networking behaviours and the career success measures. Research limitations/implications: The public sector and cultural contexts of the study may limit the generalisability of the findings. However, the paper did find that the measures used were appropriate and valid. Practical implications: The study highlights the importance of internal networking and the value of training managers in networking skills. Originality/value: The study contributes to the emerging literature on the career success of managers in non-Western countries.